HUBUNGAN PENGETAHUAN TENTANG KANKER PAYUDARA TERHADAP PERILAKU PENCEGAHAN KANKER PAYUDARA PADA WANITA USIA SUBUR DI PMB AFIIN NANIK YUMAEROH BEKASI TAHUN 2023 - Afiin Nanik Yumaeroh; Wiwit Desi Intarti; Tety Rina Aritonang (Jurnal Bina Cipta Husada, 2023)
Knowledge of women of childbearing age towards breast cancer influences behavior in breast cancer. This study aims to determine the relationship of knowledge to breast cancer prevention behavior in women of childbearing age at PMB Afiin Nanik Yumaeroh in 2023. The design of this study is quantitative with correlational techniques. The sampling used is probability sampling with a simple random sampling method. The population is 100 people. The analysis used was bivariate analysis using the Pearson chi-square test. obtained a P value of 0.023, meaning that there is significant relationship between breast cancer knowledge in women of childbearing age and breast cancer prevention behavior at PMB Afiin Nanik Yumaeroh Bekasi in 2023. It is recommended for women of childbearing age to do early detection by doing self-examination (SADARI), for married people can do breast examination by husband (SARAMI), or can do clinical examination (SADANIS).